Supporting open access, integrating distributed research platforms, and building a research information management platform - Daniel M. Coughlin; Cynthia Hudson Vitale (Code4Lib Journal, 2022)
Academic libraries are often called upon by their university communities to collect, manage, and curate information about the research activity produced at their campuses. Proper research information management (RIM) can be leveraged for multiple institutional contexts, including networking, reporting activities, building faculty profiles, and supporting the reputation management of the institution.